Hubungan Penggunaan Multimedia Interaktif Terhadap Keterampilan Passing Bolavoli - Adelia Septiani Dwi Putri; Mochamad Ridwan (Jurnal Keolahragaan, 2026)
This study aims to determine the relationship between the use of interactive multimedia and the mastery of basic volleyball passing skills among 10th-grade high school students in Gresik Regency. The method used is a quantitative correlational approach involving 33 students selected through purposive sampling. Data were collected using a questionnaire on interactive multimedia use—covering aspects from visual appeal to learning motivation—along with field-based physical tests, including the overhead pass test (AAHPER) and the underhand pass test (Brumbach). Statistical analysis was performed using the Pearson Product-Moment method via IBM SPSS Statistics 25. The results showed a correlation coefficient of r = 0.046 with a significance level of 0.800 (> 0.05), indicating no significant relationship between interactive multimedia use and students' volleyball passing skills. The benefits of interactive multimedia tend to be cognitive in nature, helping students understand movement patterns theoretically, while psychomotor mastery of volleyball passing remains highly dependent on the frequency and quality of direct physical practice. Physical education teachers are advised to integrate digital media in a balanced manner with practical field training. Penelitian ini bertujuan untuk mengetahui hubungan penggunaan multimedia interaktif terhadap penguasaan keterampilan dasar passing bolavoli siswa kelas X SMA di Kabupaten Gresik. Metode yang digunakan adalah pendekatan kuantitatif korelasional dengan melibatkan 33 siswa yang dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan angket penggunaan multimedia interaktif yang mencakup aspek kemenarikan tampilan hingga motivasi belajar, serta tes fisik berupa tes passing atas (AAHPER) dan tes passing bawah (Brumbach). Analisis data dilakukan menggunakan metode Product Moment Pearson melalui IBM SPSS Statistics 25. Hasil penelitian menunjukkan koefisien korelasi r = 0,046 dengan tingkat signifikansi 0,800 (> 0,05), yang berarti tidak terdapat hubungan yang signifikan antara penggunaan multimedia interaktif dan keterampilan passing bolavoli siswa. Manfaat multimedia interaktif cenderung lebih bersifat kognitif dalam membantu siswa memahami pola gerak secara teoretis, sementara penguasaan keterampilan psikomotorik passing bolavoli tetap sangat bergantung pada frekuensi dan kualitas latihan fisik langsung di lapangan. Guru PJOK disarankan mengintegrasikan media digital secara seimbang dengan latihan praktik nyata di lapangan.